Can "Oral Fluid" be Used Instead of "Urine" for Rapid Screening of Drug of Abuse: A Prospective Pilot Study. Issue 5 (September 2015) - Chow, ATY; Ng, VCH; Lau, FL
Introduction: Spot urine tests are commonly employed by emergency physicians in Hong Kong to detect recent abusive drug exposure. Spot tests utilising oral fluid are gaining its popularity in other parts of the world. There was lack of evidence about employment of rapid oral fluid test (ROFT) in the local emergency medical settings. The objective of this study is to determine the operating characteristics of ROFT, and to compare its agreement with the bedside urine immunoassay test (BUIT). Setting: The emergency department and the substance abuse clinic of a regional hospital. Methods: This was a single-centered cross-sectional study of diagnostic test. Patients suspected to have drug abuse were tested using either one or both of the commercially available ROFT and BUIT. The sensitivity, specificity and accuracy of both tests were calculated with reference to the laboratory urine toxicology screening results. The agreement between ROFT and BUIT was calculated. Results: For the detection of ketamine and methamphetamine (the two most prevalent abusive substances), ROFT had 72-100% sensitivity and 93-100% specificity, which were comparable to that of BUIT (74-100% sensitivity and 100% specificity). The overall observed agreement of ROFT and BUIT results was at least 96%. There was good agreement between ROFT and BUIT with kappa values of 0.90-1.00. Conclusion: In this pilot study, the operating characteristics of ROFT are comparable with that of BUIT, with both tests showing good agreements in the detection of ketamine and methamphetamine uses. ROFT can potentially be employed as an alternative investigation for rapid diagnosis of patients with suspected drug abuse. (Hong Kong j.emerg.med. 2015;22:265-269)